Food biosensors - Ahmen, Minhaz Uddin; Zourob, Mohammed; Tamilya, Eiichi (Food chemistry, function and analysis ;, 2017)
Covering all aspects of food biosensors, from how they function to the latest market applications, this book is essential reading for both new comers and experts in this field.